CORRIGENDUM (Pakistan Armed Forces Medical Journal, 2020)
Dr Gulshan Ara Trali was corresponding author of article title “Protein-Protein Interaction Analysis of Human Interferon Alpha Receptor (IFNAR-2) Protein Using String Server” Published in PAFMJ Issue of February 2020; Vol 70 (1): Page 245-52. The Address of corresponding author read as Swat Medical College, Swat Pakistan. The omission is regretted.